Growth, Yield and Water Productivity of Tomato as Influenced by Deficit Irrigation Water Management - Sangeeta Mukherjee (17789009) (2023)
The deficit irrigation offers water savings potential that is becoming popular in arid and semi-arid regions reducing freshwater use over time. A two-year factorial experiment was conducted to evaluate growth, yield and water productivity of tomato under water deficit irrigation of the drip and furrow method. The experiment was carried out in a split-plot design with drip irrigation and furrow irrigation as main plot treatments, and soil moisture regimes (0, -10, -20, -30 kPa) as subplots. Data were collected on growth parameters, physiological traits, yield and water productivity of tomato. The results showed that physiological traits, yield, and water productivity were significantly influenced by irrigation system and soil moisture regime. The drip irrigation system with -10 kPa soil moisture regime reduced total water input by 22.6% and 19.8% and gave 28% and 22% higher fruit yields in 2020 and 2021, respectively, compared with furrow irrigation system. Plant growth was higher and flowering occurred earlier (3 days) with drip irrigation system than with furrow irrigation. When the soil water content was -10 kPa, drip irrigation performed significantly better than for other soil moisture regimes by improving physiological and phenological attributes, and thereby, advancing tomato growth and fruit yield. Thus, a drip irrigation system with soil moisture regime -10 kPa could reduce total water input through precise irrigation, maximizing tomato yield and water productivity. Other Information Published in: Environmental Processes License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s40710-023-00624-z